SWEARING IN BANJARNESE: A GENDER ANALYSIS - Lestary, Agustina; Mubarraq, Yasyir Fahmi (HUMANIKA, 2019)
This study aims to analyze the swearing words used by Banjarese. The researchersÂ  apply the gender analysis as the main theoretical framework. The data of this study are swearing words commonly used by Banjarese, regardless of age or educational background. The swearing words are classified into; those mostly used by male and those used by female. The researchers draw conclusion after classifying the group of words and what they represent. Based on the findings, it is found that male and female mostly use different words to swear. Female uses wider range of words to swear in comparison to the words used by male.